Chronic Rejection and Extrahepatic Biliary Tract Obstruction 8 Years After Orthotopic Liver Transplantation Using the Gallbladder-Conduit Technique. Issue 1 (1991) - Lerut, J.; Zimmermann, A.; Gertsch, Ph.; Preisig, R.; Blumgart, L. H.
Abstract : A case of delayed biliary obstruction and cholangitis, occurring in the setting of chronic allograft rejection, 8 years after liver transplantation using the gallbladder-conduit, is presented. Extrahepatic biliary obstruction may be seen in the late follow-up of liver grafting and rejection phenomena may play a significant role in the development of such obstruction.